Pan-TRK Immunohistochemistry: A Useful Diagnostic Adjunct For Secretory Carcinoma of the Breast. (December 2019) - Harrison, Beth T.; Fowler, Elizabeth; Krings, Gregor; Chen, Yunn-Yi; Bean, Gregory R.; Vincent-Salomon, Anne; Fuhrmann, Laetitia; Barnick, Sandra E.; Chen, Beiyun; Hosfield, Elizabeth M.; Hornick, Jason L.; Schnitt, Stuart J.
Abstract : Secretory carcinoma is a special-type breast carcinoma underpinned by a recurrent t(12;15)(p13;q25) translocation resulting in ETV6-NTRK3 gene fusion. Immunohistochemistry (IHC) using a pan-TRK antibody has been recently shown to help identify NTRK rearrangements in other tumor types. The purpose of this study was to assess the diagnostic utility of pan-TRK IHC in secretory carcinoma of the breast. Pan-TRK IHC was performed using a rabbit monoclonal antibody on whole sections of 24 breast secretory carcinomas and tissue microarray sections of other breast carcinoma types (n=203) and histologic mimics (n=15). Cases were assessed for staining intensity and localization. The 24 patients with secretory carcinoma had a median age of 44 years and a median tumor size of 1.0 cm. ETV6 fluorescence in situ hybridization was positive in all cases tested (n=20). Twenty-three cases (95.8%) showed staining with pan-TRK, which was exclusively nuclear in 19, primarily nuclear with weak cytoplasmic staining in 3, and primarily cytoplasmic with focal nuclear staining in 1. The nuclear staining was diffuse in 17 and at least focally strong in 17. The only pan-TRK negative case was a core biopsy with limited tumor. Among the 203 nonsecretory carcinomas, 21 (10.3%) showed focal, weak nuclear staining in <5% of tumor cells and 1 (0.5%) showed focal membranous staining. All histologic mimics were negative. In conclusion, diffuse and/or at least focally strong nuclear pan-TRK staining is a sensitive and specific marker for secretory carcinoma of the breast.